Effect Of pH Condition During Hydrothermal Synthesis On The Properties Of Hydroxyapatite From Eggshell Waste - Abd Rahim, Toibah; Misran, Fatimah; Shaaban, Azizah; Mustafa, Zaleha (Penerbit UMP Press, 2019)
Hydroxyapatite (HA) powders were synthesized using eggshell waste through hydrothermal method to develop bioceramics materials for medical applications. The effects of the pH conditions during the synthesis on the phase behaviour, crystallite size, crystallinity and morphology of as-synthesized ceramic powders were evaluated. The XRD patterns showed that HA was the only main phase present in the as-synthesized powder after being calcined at 400°C. However, EDX measurement detected the presence of Mg as trace element which originated from the eggshell as starting materials. The crystallite size and crystallinity of the HA powders were increased when the powders were synthesized in acidic condition as compared to basic condition. FESEM images showed that HA powder with nano-sized rods and spherical morphologies were obtained from the powders that were synthesized at pH 5, while the powder particles synthesized at the basic condition at pH 9 produced elongated rodshape particles. The PSD results showed that the synthesized HA was in agglomerated form which was also confirmed by FESEM images.